Beyond Statistical Learning: Communication Principles and Language Internal Factors Shape Grammar in Child and Adult Beginners Learning Polish Through Controlled Exposure. Issue 4 (5th June 2018) - Dimroth, Christine
Abstract: This study investigated the predictions of two approaches to second language acquisition. According to the usage‐based approach, learner knowledge results from the strengths and weaknesses of input‐driven statistical learning. According to the learner‐varieties approach, pragmatic communication principles and language‐internal constraints play major roles in language development. For this study, novice child and adult learners of Polish (speakers of Italian or German) attended several controlled‐exposure sessions and retold a story after 14 hours of target language contact. Analyses focused on form–function associations in the learners' production data and on comparisons with properties of the input that the learners had encountered. In addition to support for input‐driven factors, there was evidence for a uniform syntax, for individual creative constructions, and for reinterpreted morphological variation, pointing to an influence of communication principles and to an effect of system‐internal factors. Findings revealed differences due to learners' age but not their language background.